The destruction of river pearl mussels in Hukkajoki : A case study of state-corporate environmental crime in the Finnish logging industry - Kleine, Yrjö; Vääriskoski, Sakari; Riitala, Sirkku (My University, 2025)
This case study reviews the destruction of over a thousand endangered river pearl mussels by Stora Enso, a Finnish forestry corporate giant. The case is currently being investigated by the Finnish police as an aggravated environmental conservation crime. We will study the public, political and criminal justice reactions to the crime as well as the circumstances that led to it. We will also study the relationship between the Finnish state and the forest industry, as well as the state of Finnish laws and regulations regarding logging. Our findings are that there exists a regime of permission between the Finnish government and the forest industry. It is made possible through lax forestry law and compliance regulation. The results are constant environmental crimes committed by the logging industry, that only really get noticed when a moment of rupture like the Hukkajoki case occurs. We propose stricter regulations and call for societal awareness and vigilance on the matter. This case study is based on news by Yle, Helsingin Sanomat and others. Our key source on the problems of the PEFC certificate system is the Yle MOT document “Tuhotun metsän tarina”, a part of the ICIJ investigation “Deforestation Inc.” The theoretical base for our case study is the state- corporate crime theory coined by R. C. Kramer. Other key concepts in our theoretical framework are Acts of Omission as defined by D. Kauzlarich and R. White and points of rupture and regimes of permission as defined by D. Whyte and I. Bernat.

Tämä tapaustutkimus käsittelee Stora Enson aiheuttamaa raakkutuhoa, jossa kuoli yli tuhat uhanalaista jokihelmisimpukkaa eli raakkua. Poliisi tutkii tällä hetkellä tapausta törkeänä luonnonsuojelurikoksena. Tutkimme rikoksen julkista, poliittista ja rikosoikeudellista käsittelyä samoin kuin rikokseen vaikuttaneita olosuhteita. Tutkimme myös Suomen valtion ja metsäteollisuuden välistä suhdetta sekä hakkuita sääntelevää lakia ja muuta sääntelyä. Tuloksemme on, että Suomen valtion ja metsäteollisuuden välillä on olemassa sallivuuden järjestelmä, “regime of permission”, joka johtaa metsäyhtiöiden hakkuissa tekemiin jatkuviin ympäristörikoksiin. Näistä rikoksista Hukkajoki on vain jäänvuoren huippu, repeämispiste. Järjestelmän mahdollistavat löyhä metsälaki ja vapaaehtoinen sääntely. Ratkaisuksi ehdotamme tiukempaa sääntelyä ja toivomme yhteiskunnallista valppautta ja aktiivisuutta asian suhteen. Tapaustutkimus perustuu Ylen, Helsingin Sanomien ja muiden lehtien uutisiin. Tärkein lähteemme PEFC-sertifikaatin ongelmista on Yle MOT:n dokumentti “Tuhotun metsän tarina”, joka on osa ICIJ:n kansainvälistä selvitystä “Deforestation Inc.” Tutkimuksen teoreettinen pohja perustuu R. C. Kramerin kehittämään teoriaan “valtioiden ja yhtiöiden välisestä organisaatiorikollisuudesta”. Muita avainelementtejä tutkimuksessamme ovat “peitesääntely” D. Kauzlarichia ja R. Whiteä mukaillen, sekä D. Whyten ja I. Bernatin määrittelemät “repeämispisteet” ja “sallivuuden järjestelmät”.
Keywords: state-corporate crime, environmental crime, logging, Forest Act